Efisiensi Chiller Gedung Produksi Cat Pt. X - Muhammad Fatah, Fadel; Trisno, Ramon (Jurnal Etnik: Ekonomi-Teknik, 2023)
Refrigeration machines and air conditioning machines are an inseparable part of human life in improving the quality of activities. using air conditioning(Air Conditioning). Refrigeration systems in large buildings or those used to cool production machines in the industrial world require energy efficiency. This study uses the CLTD methodCooling Load Temperatur Difference Calculation of heat from each internal and external load of the room refers to the standard ASHRAE Cooling Load Calculation. With the calculation of heat on walls, roofs and floors, it is included in the calculation of external heat loads and the heat of occupants, equipment and lighting is included in internal heat and heat from infiltration and ventilation. Some of the parameter factors considered include heat from building walls, building roofs, building floors, heat in humans working inside, lighting used, production parameters and infiltration factors, ventilation. The value of COcontractualfor chiller 1 it was 6.47 and for chiller 2 it was 8.07. While the value of COPrefrigran is 7.8 for chiller 1 and chiller 2 which is 9.7. The efficiency obtained from these two units is chiller 1 57.4% and chiller 2 58.8%. From the calculation of the cooling load carried out, it is obtained 275576 ??BTU/hr or 330691 BTH/hr after adding 20% ??so that the engine is not burdened, if it is known that 1 kW = 3410 BTU/hr then the cooling load is 97kW.